PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - shinta sunny; Herlina Usman; Monica Bellandina A; Ananda Putri (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to develop electronic Student Worksheets based on Problem Based Learning (PBL) in science learning on ecosystem material for fifth-grade elementary school students and also to determine the feasibility of electronic Student Worksheets based on Problem Based Learning (PBL). The research method used is Research and Development or R&D. The research model used is Borg and Gall. The Borg and Gall model applies ten stages of research and development, according to Effendi and Hendriyani, these stages are (1) research and information collecting, (2) planning, (3) developing preliminary product, (4) preliminary field testing, (5) main product revision, (6) main field testing, (7) operational product revision, (8) operational field testing, (9) final product revision, (10) dissemination and implementation. Due to various aspects of consideration, including cost and time, the simplification of research and development is carried out only up to the ninth stage. The instruments for collecting data were expert test questionnaires and student response questionnaires. The expert test process was carried out on media experts and science material experts. The validation result of the media expert test was 84% so it could be said to be